Inventory Of Randang Lokan Recipes In Nagari Sasak Kecamatan Sasak Ranah Pesisir District Pasaman Barat - Hilma Yunifa; Wiwik Gusnita (Universitas Negeri Padang, 2021)
This study aims to inventory the randanglokan recipe, identify the materials used for the production of randanglokan, identify the equipment used, explain the processing process, and describe the function of the randanglokan in the Sasak village. This type of research is a descriptive study with a qualitative approach method. Data collection techniques were carried out in the form of observation, interviews, and documentation in the field. After data collection, the authors obtained specific research findings, these findings were in accordance with the research objectives, the first was about the ingredients for making randanglokan in the form of: lokan, coconut milk, shallots, garlic, ginger, galangal, lemongrass, coriander, turmeric leaves, and leaves. greetings, tapak leman leaves, lime leaves, red chilies, cayenne pepper, turmeric, tamarind, lime, and salt. The second finding is in the form of tools used in processing, namely: iron cauldrons, milled stones, clay stoves, stone stoves, spoons, tenong. Furthermore, the processing process starts from material preparation until it is ready to be served. The latter is the function of the randanglokan, which is served at events such as wedding receptions, circumcision of the apostle, commemoration of Islamic holidays, welcoming the holy month of Ramadan, and meals for visits from officials